Prenatal and Postnatal Follow-up in Trisomies 13 and 18: A 20-Year Experience in a Tertiary Center - Akgün Doğan, Özlem; Ürel Demir, Gizem; Arslan, Umut; Şimşek-Kiper, Pelin Özlem; Utine, Gülen Eda; Alikaşifoğlu, Mehmet; Boduroğlu, Koray (American Journal of Perinatology, 2018)
Objective Trisomies 13 and 18 are among the most common autosomal aneuploidies associated with high mortality rates. Conventional management strategies offer to limit interventional support; however, some of the recent studies suggest that intervention does make a difference in terms of survival.Study Design A retrospective cohort study was performed between January 1996 and January 2016, covering all cases with such trisomies. A total of 69 cases were reviewed for clinical aspects, outcome, and management strategies.Results In almost all pregnancies with follow-up, at least one indication present for invasive testing (54/55). Invasive testing was not performed in 18.5% of such cases. All parents opted for termination in cases with prenatal diagnosis. None of the liveborns had prenatal diagnoses, thus, neonatal resuscitation and intensive care unit admission were not withheld in such infants. Major intervention was done in only one patient with full trisomy 13. Median survival for infants with full trisomies 13 and 18 was 36 and 60 days, respectively. Almost half the patients died within 1 month.Conclusion To which extent the major interventions should be withheld is an issue of debate in managing such infants; however, current approaches are subject to change, given the technological advances.
Keywords: trisomy 13; trisomy 18; prenatal counseling; intervention; outcome